Detection of fluoroquinolone and sulfonamide residues in poultry eggs in Kunming city, southwest China - Wang, Rui; Zhang, Chen-Xi; Li, Zhuo-Yang; Zheng, Zhi-Yuan; Xiang, Yi; Liu, Yang; Zhao, Rong-Fang; Fang, Jing (Poultry science, 2022)
Antibiotic residues contained in poultry eggs pose threat to human health. However, the classes and concentrations of antibiotics in poultry egg in southwestern China is unknown due to insufficient monitoring and research. A total of 513 egg samples were collected from supermarkets and farm markets in Kunming city in 2020 and the levels of 7 antibiotics were analyzed using ultra high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method. The linear correlation coefficients were above 0.990 for all antibiotics tested. The limits of detection and limits of quantification in poultry eggs were 0.002 to 0.010 μg/g and 0.007 to 0.033 μg/g, respectively. The average recoveries of the 7 analytes from poultry egg samples were 80.00 to 128.01%, with relative standard deviations of less than 13.97%. A total of 93 (18.13%) samples tested positive for antibiotics, with the highest concentration being 2.48 μg/g. The concentration range of ofloxacin, danofloxacin, difloxacin, sulfadimethoxine, sulfamonomethoxine, sulfamethoxypyridazine, and sulfamethoxazole in poultry eggs was 0.01 to 0.37 μg/g, 0.06 to 0.48 μg/g, 0.05 to 0.29 μg/g, 0.03 to 0.16 μg/g, 0.06 to 1.00 μg/g, 0.05 to 0.37, and 0.07 to 2.48 μg/g, respectively. Sulfamonomethoxine was detected from hen eggs with the highest concentration level at 1.00 μg/g. Sulfamethoxazole was detected with the highest concentration level from both duck and quail eggs, at 1.87 and 2.48 μg/g, respectively. The antibiotic with the highest residue level in pheasant eggs was danofloxacin, which was 0.37 μg/g. Sulfamethoxypyridazine was identified in 30 samples with the highest positive rate of 5.85%, sulfadimethoxine was identified in 3 samples with the lowest positive rate of 0.58%. We observed that 7 targeted antibiotic residues in quail eggs and 3 targeted antibiotic residues in pheasant eggs. We also found that there were antibiotic residues in free-range hen eggs and the concentration was not low. The antibiotic with the highest residue level in free-range eggs was sulfamonomethoxine, which was 1.00 μg/g. These findings suggest that continual antibiotic residue monitoring of poultry eggs is essential in China.